Nutrition incentives in dairy contract farming in northern Senegal - Bernard, Tanguy; Hidrobo, Melissa; Le Port, Agnès; Rawat, Rahul (International Food Policy Research Institute, 2017)
Health-related incentives to reward effort or commitment are commonplace in many professional contracts throughout the world. Typically absent from small-scale agriculture in poor countries, such incentives may help overcome both health issues for remote rural families and supply issues for firms. Using a randomized control design, we investigate the impact of adding a micronutrient-fortified product in contracts between a Senegalese dairy processing factory and its seminomadic milk suppliers. Findings show significant increases in frequency of delivery but only limited impacts on total milk delivered. These impacts are time sensitive and limited mostly to households where women are more in control of milk contracts.